A Proposed Program from the Perspective of the General Practice of Social Work to Overcome Husbands' Violence Against Their Wives (Journal of the College of Education for Women, 2022)
Husbands’ violence towards their wives is one of the greatly important issues in social sciences. Accordingly, the current study aims at determining the levels of violence practiced by husbands towards their wives to propose a professional program from the perspective of the general practice of social work to overcome such a phenomenon. The study is descriptive in nature, where the researcher has used a comprehensive social survey method. To achieve the goal of the study, the researcher has prepared a questionnaire that consisted of two parts. The first part contains the primary data of the two sections, and the second contains (38) phrases distributed over four axes to measure the levels and types of violence among the sample’s members. The study has been conducted in the Safety House to Care for Abused Women in Gaza. The study’s sample amounted to (26) battered women. The results have revealed that the level of psychological violence is the most prevalent (81.3%), then comes physical violence (68.6%), then social (68%), and finally, comes economic violence (66.6%). The Study concluded that there are statistically significant differences between the level of violence practiced by husbands towards their wives in the Safety House for the care of battered women according to the variables of wife's educational status, and number of children. In light of these results, the study has concluded a proposed program from the perspective of general public practice to overcome husbands' violence against their wives.